2024
DOI: 10.1007/s10570-023-05726-3
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated cellulose in additive manufacturing

Irina Garces,
Tri-Dung Ngo,
Cagri Ayranci
et al.

Abstract: Environmental concerns within the 3D printing industry have attracted interest in finding biodegradable, eco-friendly material solutions. Cellulose is the most abundant natural polymer on the planet. Cellulosic pulp, derived from biomass, can be dissolved in eco-friendly solvents such as N-methyl morpholine N-oxide (NMMO) to produce Lyocell TM . Lyocell TM has had applications in the textile industry for the last decade. It has shown promise in producing highquality cellulosic fibers and the ability to be alte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…A detailed study on the capillary extrusion of cellulose-NMMO solutions was previously reported. 12 The shear viscosity, η, and first normal stress difference, N 1 , of 7.0% cellulose in the NMMO solution were measured as a function of shear rate, γȧ t different temperatures (Figure 1a). The sample showed a shear thinning behavior at all measured temperatures (80−130 °C) above the shear rate of 10 −1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed study on the capillary extrusion of cellulose-NMMO solutions was previously reported. 12 The shear viscosity, η, and first normal stress difference, N 1 , of 7.0% cellulose in the NMMO solution were measured as a function of shear rate, γȧ t different temperatures (Figure 1a). The sample showed a shear thinning behavior at all measured temperatures (80−130 °C) above the shear rate of 10 −1 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Immediately after, the dope was removed from the vessel and stored in a lab refrigerator at 5 °C for further experiments. 12 All of the 3D printing experiments were carried out by using a dope from a single batch of preparation. Thus, the effects of possible variations in dissolving the cellulose further postextrusion were minimized.…”
Section: Dissolvingmentioning
confidence: 99%
See 2 more Smart Citations
“…Many other scientists and researchers, such as Hod Lipson, Neil Gershenfeld, Terry Wohlers, Elaine Cohen, and Jean-Claude André, have also made significant contributions, advancing various aspects of 3D printing through their work on specific mathematical modelling techniques. Some current applications involve characterizing the shear thinning behavior of inks by quantifying the degree of shear thinning and using mathematical models to predict the window of printer operating parameters within which Overall, each group of topics concerning 3D printing in an ecological context has the potential to contribute to a more sustainable manufacturing industry by reducing material and energy use and carbon emissions [6,[55][56][57]; conserving resources [7,58,59], repairing and upcycling [56,[60][61][62] and reducing waste generation [63][64][65][66]; facilitating the selection of eco-friendly materials [67][68][69][70][71]; and enabling decentralized and customized production processes [72][73][74], thus contributing to holistic assessments of environmental impacts. In the group of publications related to modelling, there is a significant emphasis on understanding printing conditions and the properties of various printed materials.…”
Section: History: Bridging Innovation With Environmental Sustainabilitymentioning
confidence: 99%